2013
DOI: 10.1007/s40123-012-0009-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Retinal Nerve Fiber Layer Changes with Oral Isotretinoin Treatment

Abstract: IntroductionCentral nervous system toxicity is a well-known side effect of isotretinoin treatment. The aim of this study was to establish the effects of isotretinoin on retinal nerve fiber layer (RNFL) thickness.Materials and MethodsStudy subjects received oral isotretinoin treatment for nodulocystic acne. All patients underwent a detailed ophthalmologic examination including best-corrected visual acuity, slit-lamp examination, tonometry, color vision assessment, fundoscopy, and RNFL measurement. RNFL measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…Ucak et al [13] reported the possible toxic effects of isotretinoinon RNFL, especially in the temporal layer. In the study conducted by Kapti et al [14] It is reported that isotretinoin has no effect on RNFL thickness We did not find a statistically significant difference in RNFL thickness in our study. Sari et al [9] investigated the optical nerve function, both clinically and in vision field test in patients treated with oral tretinoin and have not observed any differences in the same findings during 5.5 months.…”
Section: Discussioncontrasting
confidence: 82%
“…Ucak et al [13] reported the possible toxic effects of isotretinoinon RNFL, especially in the temporal layer. In the study conducted by Kapti et al [14] It is reported that isotretinoin has no effect on RNFL thickness We did not find a statistically significant difference in RNFL thickness in our study. Sari et al [9] investigated the optical nerve function, both clinically and in vision field test in patients treated with oral tretinoin and have not observed any differences in the same findings during 5.5 months.…”
Section: Discussioncontrasting
confidence: 82%
“…29 Nevertheless, other studies evaluating the RNFL and GCC thickness after systemic isotretinoin use for 6 and 12 months, respectively, found no significant differences. 5,30 Other retina-related complications including vascular occlusions, 31 premacular hemorrhage, 32 serous retinal detachment, 33 and vitreous disturbance have been reported. 24 However, none of the side effects mentioned above fulfills the WHO criteria mentioned above to be considered as "certain."…”
Section: Other Ocular Adverse Effectsmentioning
confidence: 99%
“…In the literature, studies investigating the effects of isotretinoin treatment on RNFL thickness show different results. Kapti et al7 found no significant difference in RNFL thickness in the 6-month follow-up of patients who received systemic isotretinoin treatment compared to pretreatment. Sekeryapan et al6 examined the changes in RNFL and ganglion cell complex in patients receiving 1 mg/kg/day oral isotretinoin treatment and reported that systemic isotretinoin treatment had no negative effect on RNFL thickness and ganglion cell complex.…”
mentioning
confidence: 96%